(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The Boletín Oficial del Estado published the 25 of May, the organic law 6/2007,of modification of organic law 2/1979, of 3 of October of the Constitutional Court.The present reform tries to approach some opened subjects of the norm and specially to solve the difficulties of operation of the Constitutional Court. From its creation, the operation of the Court has gone gradually expressing certain difficulties, mainly of procedural scope, that prevent the exercise of the functions that the Constitutiongrants to him like supreme guarantor of the legal ordering. Objective of the present study is to analyze the reach of the last reform being started off of a briefanalysis of the competitions that confer our Court.